2015
DOI: 10.1137/140981046
|View full text |Cite
|
Sign up to set email alerts
|

How Superadditive Can a Risk Measure Be?

Abstract: This is the accepted version of the paper.This version of the publication may differ from the final published version. Abstract In this paper, we study the extent to which any risk measure can lead to superadditive risk assessments, implying the potential for penalizing portfolio diversification. For this purpose we introduce the notion of extreme-aggregation risk measures. The extreme-aggregation measure characterizes the most superadditive behavior of a risk measure, by yielding the worst-possible diversific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 30 publications
(15 citation statements)
references
References 42 publications
0
15
0
Order By: Relevance
“…The following simple lemma is a combination of theorem 4.1 and corollary 4.2 of Wang et al. (). Lemma The smallest law‐invariant coherent risk measure dominating ρv exists, and it is given by ρvfalse(Xfalse)=trueprefixsupμscriptPv0true01 ES pfalse(Xfalse)dμfalse(pfalse),XL1,where scriptPv=false{μscriptP:v(μ)<+false}.…”
Section: Asymptotic Equivalence For Convex Risk Measuresmentioning
confidence: 86%
See 4 more Smart Citations
“…The following simple lemma is a combination of theorem 4.1 and corollary 4.2 of Wang et al. (). Lemma The smallest law‐invariant coherent risk measure dominating ρv exists, and it is given by ρvfalse(Xfalse)=trueprefixsupμscriptPv0true01 ES pfalse(Xfalse)dμfalse(pfalse),XL1,where scriptPv=false{μscriptP:v(μ)<+false}.…”
Section: Asymptotic Equivalence For Convex Risk Measuresmentioning
confidence: 86%
“…It was given in Wang et al. () for right continuous hH; however, from there, it is a simple exercise to see that the lemma holds for all hH. In the latter paper, it is also shown that ρh is the smallest law‐invariant coherent risk measure dominating ρh.…”
Section: Asymptotic Equivalence For Distortion Risk Measuresmentioning
confidence: 88%
See 3 more Smart Citations